The role of active DNA demethylation and Tet enzyme function in memory formation and cocaine action. (20th June 2016) - Alaghband, Yasaman; Bredy, Timothy W.; Wood, Marcelo A.
Abstract: Active DNA modification is a major epigenetic mechanism that regulates gene expression in an experience-dependent manner, which is thought to establish stable changes in neuronal function and behavior. Recent discoveries regarding the Ten eleven translocation (Tet1-3) family of DNA hydroxylases have provided a new avenue for the study of active DNA demethylation, and may thus help to advance our understanding of how dynamic DNA modifications lead to long-lasting changes in brain regions underlying learning and memory, as well as drug-seeking and propensity for relapse following abstinence. Drug addiction is a complex, relapsing disorder in which compulsive drug-seeking behavior can persist despite aversive consequences. Therefore, understanding the molecular mechanisms that underlie the onset and persistence of drug addiction, as well as the pronounced propensity for relapse observed in addicts, is necessary for the development of selective treatments and therapies. In this mini-review, we provide an overview of the involvement of active DNA demethylation with an emphasis on the Tet family of enzymes and 5-hydroxymethylcytosine (5-hmC) in learning and memory, as well as in drug-seeking behavior. Memory and addiction share overlapping molecular, cellular, and circuit functions allowing research in one area to inform the other. Current discrepancies and directions for future studies focusing on the dynamic interplay between DNA methylation and demethylation, and how they orchestrate gene expression required for neuronal plasticity underlying memory formation, are discussed.